(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this study is to further understand the phenomenon of psychological resilience, specifically its relationship to group cohesion within an educational settingng college students. We applied Quantitative Method research in trm of surveys composed of the Connor-Davidson Psychological Resilience Scale (CD-RISC-25) and Nelson Laird’s school engagement scale. Semi-structured interview questionnaires were also used. This study surveyed over 400 students various universities in Ho Chi Minh City, including Hoa Sen University; Social Science and Humanities; Ho Chi Minh City Medicine and Pharmacy University; Pham Ngọc Thach University; Vang Lang University; HUTECH University; FPT Professional College, Economics and Law; and Ho Chi Minh City University of Finance and Marketing in Vietnam. From those surveyed, we can conclude that student resiliencehi Furthermo issitorrelation between psygical resilience in students and school engagement. The interview results demonstrate that life challenges affect students’ psychologicsilience. New findings in this research serve as the foundation for the development of intervention programs to improve students’ psychological resilience, thereby improving the learning environment.